Addressing for 6LoWPAN based on multi-hop clusters. (2017) - Wang, Dong; Wang, Xiaonan; Dou, Zhengxiong
6LoWPAN is a multi-hop network, so the address configuration standards commonly used in single-hop IP networks cannot directly be applied in 6LoWPAN. In this situation, some addressing solutions for 6LoWPAN are proposed. Since these solutions employ the stateless strategy such as duplicate address detection (DAD) or the stateful strategy such as a remote server, the addressing cost and latency are relatively high. This paper proposes an addressing scheme based on multi-hop clusters and aims to reduce the total addressing cost and delay. In this scheme, a cluster covers a multi-hop area, so the frequency of a node performing the addressing is lowered and the total addressing cost and delay are reduced. Moreover, a node employs beacons to obtain a unique address from a neighbour without DAD, so the addressing cost and delay are further reduced. This scheme is evaluated, and the data results show that the average addressing success rate is increased and the total addressing cost and delay are reduced.